Primary cardiac angiosarcoma: a rare cause of diffuse alveolar haemorrhage - Palkar, Atul Vijay (BMJ Case Rep, 2018)
Primary cardiac angiosarcoma is a rare disease with a dismal prognosis. We report a case of a 50-year-old man who presented with haemoptysis, cough and worsening dyspnoea. An intracardiac mass was visualised on echocardiogram. He was treated for diffuse alveolar haemorrhage and acute respiratory distress syndrome but died from refractory hypoxaemic respiratory failure leading to cardiac arrest. The diagnosis of primary cardiac angiosarcoma with haemorrhagic pulmonary metastases leading to diffuse alveolar damage was confirmed on autopsy.